Sejarah Dan Pemikiran Kaum Injili Di Tengah-Tengah Perubahan Dan Tantangan Zaman - Enggar Objantoro (Sekolah Tinggi Teologi Simpson, 2017)
Enggar Objantoro, History and Thought of Evangelicals Amidst the Changes and Challenges of the Age. In this paper the author discusses the existence and challenges that are being and will be faced by evangelicals, especially in Indonesia. To be able to describe what the purpose of the study, the author uses the descriptive research literature study. The analysis in this study focuses on the interpretation of written materials in accordance with the context. To maintain credibility, the authors use authentic and published literature material. The results of this study show that the presence of evangelicals in some places has interesting characteristics to investigate, as in America can not be released with Fundamentalism. Then evangelicals in Europe have existed since the time of reform, because evangelicals are understood as reformed churches. In 1842 the UK also established the European Evangelical Alliance, which has contributed to the formation of the evangelical movement in Europe. The rise of evangelicals in Indonesia is also inseparable from the evangelical movement in America. Several evangelical mission organizations are present in Indonesia. The evangelicals are in the midst of the changing times that are influenced by various understandings. Responding to the changing times there are several things that evangelicals need to do: hold fast to God's truth, open to other views without going with the flow, active in conveying ideas. Enggar Objantoro, Sejarah Dan Pemikiran Kaum Injili Di Tengah-Tengah Perubahan Dan Tantangan Zaman. Dalam paper ini penulis membahas tentang eksistensi dan tantangan-tantangan yang sedang dan akan dihadapi kaum Injili, khususnya di Indonesia. Untuk dapat menguraikan apa yang menjadi tujuan penelitian, penulis menggunakan jenis penelitian deskriptif studi pustaka. Analisis dalam penelitian ini menitikberatkan pada intepretasi pada bahan tertulis sesuai dengan konteksnya. Untuk menjaga kredibilitas, penulis menggunakan bahan literatur yang otentik dan terpublikasi. Hasil dari penelitian ini menujukkan bahwa kehadiran kaum Injili di beberapa tempat mempunyai karakteristik yang menarik untuk diselidiki, seperti di Amerika tidak dapat dilepaskan dengan Fundamentalisme. Kemudian kaum Injili di Eropa sudah ada sejak zaman reformasi, sebab kaum Injili dimengerti sebagai gereja-gereja hasil reformasi. Pada tahun 1842 di Inggris juga telah dibentuk European Evangelical Alliance, yang telah memberi kontribusi terbentuknya gerakan Injili di Eropa. Munculnya kaum Injili di Indonesia juga tidak dapat dilepaskan dari gerakan Injili di Amerika. Beberapa organisasi misi Injili hadir di Indonesia. Kaum Injili ada di tengah-tengah perubahan zaman yang dipengaruhi oleh berbagai paham-paham. Menyikapi perubahan zaman ada beberapa hal yang perlu dilakukan kaum Injili: berpegang teguh kepada kebenaran Allah, terbuka kepada pandangan lain tanpa ikut arus, aktif dalam menyampaikan gagasan.